Proceedings 14th International Parallel and Distributed Processing Symposium. IPDPS 2000
DOI: 10.1109/ipdps.2000.845989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of P/sup 3/T+: a performance estimator for distributed and parallel applications

Abstract: In this paper, we report on experiences with P 3 T +, a performance estimator for distributed and parallel programs which is used to examine at compile time the performance outcome of changes in code, problem and machine sizes, and target architectures. P 3 T + computes a variety of performance parameters including work distribution, number of transfers, amount of data transferred, transfer times, computation times, and number of cache misses. It is unique in that it models programs, code transformations, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the set of studies related to performance monitoring, analysis and tuning we have found tools that make a trace-based analysis, such as Kappa-Pi [9] and EXPERT [10], along with other studies based on static prediction, such as P 3 T+ [11], which predicts performance mainly based on information gathered at compilation time.…”
Section: Related Studiesmentioning
confidence: 99%
“…In the set of studies related to performance monitoring, analysis and tuning we have found tools that make a trace-based analysis, such as Kappa-Pi [9] and EXPERT [10], along with other studies based on static prediction, such as P 3 T+ [11], which predicts performance mainly based on information gathered at compilation time.…”
Section: Related Studiesmentioning
confidence: 99%
“…This is because the output of a symbolic execution is more informative than that of executing a concrete input, as a symbolic input represents more than one element of the input domain. In recent years, symbolic execution techniques have been studied intensively not only in software engineering, but also in the areas of programming languages and high-performance compilers [9], [25], [26], [27], [29], [36]. Sophisticated techniques and automated tools for symbolic-analysis and pathconstraint simplifications have been developed to facilitate more effective parallelism and optimization of programs.…”
Section: Introductionmentioning
confidence: 99%